Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1420-9101.2010.01991.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual coevolution in the traumatically inseminating plant bug genus Coridromius

Abstract: Sexual conflict has recently been proposed as a driving force behind the rapid diversification of genitalia among sexually reproducing organisms. In traumatically inseminating insects, males stab females in the side of the body with needle‐like genitalia, ejaculating into their body cavity. Such mating is costly to females and has led to the evolution of cost‐reducing ‘paragenitalia’ in some species. Whereas some consider this evidence of sexually antagonistic coevolution, others remain unconvinced. Variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 29 publications
0
44
0
1
Order By: Relevance
“…Critically, both mechanisms predict the coevolution of male and female genital morphology. Although there is some evidence from comparative studies of correlated patterns of evolution in male and female genital morphology [13][14][15][16][17][18] , and much work has explored patterns of phenotypic and genetic variation in male genital morphology 3,19 , few studies have focused on female genitalia. Two recent studies have suggested that female genitalia can evolve rapidly 20 and can sometimes be even more variable than male genitalia 21 .…”
mentioning
confidence: 99%
“…Critically, both mechanisms predict the coevolution of male and female genital morphology. Although there is some evidence from comparative studies of correlated patterns of evolution in male and female genital morphology [13][14][15][16][17][18] , and much work has explored patterns of phenotypic and genetic variation in male genital morphology 3,19 , few studies have focused on female genitalia. Two recent studies have suggested that female genitalia can evolve rapidly 20 and can sometimes be even more variable than male genitalia 21 .…”
mentioning
confidence: 99%
“…22). This pattern is similar to Coridromius, which is distributed in Indo-Pacific although its two main subclades are largely divided at Wallacea (Tatarnic and Cassis, 2010).…”
Section: Taxonomymentioning
confidence: 55%
“…The genus belongs to the morphologically heterogeneous subfamily Bryocorinae, for which we recently erected a new tribe-the Felisacini . Felisacus has an Indo-Pacific distribution (Schuh and Stonedahl, 1986), a pattern that is repeated for other mirid genera, including Helopeltis Signoret, 1858 (Stonedahl, 1991), Coridromius Signoret, 1862 (Tatarnic and Cassis, 2010), Ragwelellus Odhiambo, 1962 , Peritropis Uhler, 1891 (Gorcyza, 2000;Moulds and Cassis, 2006) and Pseudoloxops Kirkaldy, 1905(Schuh, 1995Schuh, 2002Schuh, -2013.…”
Section: Introductionmentioning
confidence: 99%
“…Coridromius species exhibit a Wallacean distribution, with distinct, phylogeneticlly supported eastern and western species groups (Tatarnic & cassis 2010). species in the eastern group are most easily recognized by their unilobate proepimeron, as well as the generally triangular shape of the right paramere, while those of the western group exhibit a bilobed proepimeron and the right paramere is usually (though not always) club-shaped with a thumb-or spinelike apophysis.…”
Section: Discussionmentioning
confidence: 99%
“…Coridromius is unique among the Miridae in that all species mate via traumatic insemination, whereby males use their hypodermic intromittent organ (formed by coupling of the left paramere with the aedeagus as in bed bugs -see carayon 1966) to stab females in the abdomen during mating, completely bypassing the female genitalia (Tatarnic et al 2006). Presumably in response to the costs associated with traumatic insemination (for discussion of related costs in bed bugs, see Morrow & arnqvist 2003;reinhardt et al 2003;sivaJothy 2006), females of several species have evolved paragenital structures at the site of insemination (Tatarnic et al 2006;Tatarnic & cassis 2008;Tatarnic & cassis 2010), analogous to the ectospermalege and mesospermalege of bedbugs (carayon 1966).…”
Section: Introductionmentioning
confidence: 99%